Les régions urbaines en Belgique - Lieve Vanderstraeten; Etienne Van Hecke (Belgeo)
The Belgian urban regions were defined for the first time in the early 1970s. Later on they were updated based on the censuses of 1981, 1991 and 2001. The current update is based on administrative data varying between 2014 and 2017. In 2017, 19 cities in Belgium developed an urban region with on the one hand an agglomeration (a zone of uninterrupted built environment) and on the other hand an urban fringe (a zone of more dispersed residential settlements but with a strong focus of the population on the agglomeration). The Belgian urban regions concentrate 56% of the population and 64% of the employment. After a long period of a netto exodus from the centres of the urban regions in Belgium, one can see a growth of the population of the centers between 2001 and 2017. Immigration from abroad plays an important role in this netto growth, but more issues are at stake. A final important reversal takes place in the periphery of the urban regions. Between 1970 and 2001, the growth of the populations in the urban fringes was twice as high compared to the growth in the commuter zones. Between 2001 and 2017, an equal growth in both zones took place, meaning that the sprawl of the population did not stop and takes as much place at a longer distance from the centres of the urban regions then at a shorter distance.